2021
DOI: 10.3390/ijms22179374
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Aripiprazole in the 5xFAD Alzheimer’s Disease Mouse Model

Abstract: Global aging has led to growing health concerns posed by Alzheimer’s disease (AD), the most common type of dementia. Aripiprazole is an atypical FDA-approved anti-psychotic drug with potential against AD. To investigate its therapeutic effects on AD pathology, we administered aripiprazole to 5xFAD AD model mice and examined beta-amyloid (βA)-induced AD-like phenotypes, including βA production, neuroinflammation, and cerebral glucose metabolism. Aripiprazole administration significantly decreased βA accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…ARI treatment in several rodent models led to decreased IBA1 protein expression [ 23 , 24 , 40 ]. IBA1 protein is specifically expressed in brain microglia and macrophages and is upregulated during their activation [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARI treatment in several rodent models led to decreased IBA1 protein expression [ 23 , 24 , 40 ]. IBA1 protein is specifically expressed in brain microglia and macrophages and is upregulated during their activation [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in rodents have shown that both ARI and TRZ affect brain tissue through unique signaling pathways and their effects are not always directly related to their binding on dopaminergic and serotonergic receptors [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. ARI has been shown to have neuroprotective effects in stroke recovery by promoting dopaminergic survival and neuroprotective effects in a mouse model of Alzheimer’s Disease [ 23 , 24 ]. While many studies using rodent models have shown the therapeutic effects of ARI and TRZ in different pathological conditions, there are limited reports describing their biochemical effects in healthy mice.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some promise in utilizing the lipid-lowering medication gemfibrozil which activates PPAR-α and was shown to both inhibit the production of Aβ via upregulation of ADAM10 and stimulate cellular clearance by inducing lysosomal biogenesis in the 5XFAD transgenic model of AD [33][34][35][36][37]. In a phase II parallel-design, double-blind, placebo-controlled trial targeting predementia AD, there was a significant decline on the CANS-MCI cognitive battery, and almost statistically significant declines in Aβ 42 levels and hippocampal atrophy [38].…”
Section: Alpha Secretase Activatorsmentioning
confidence: 99%